Every child, every classroom, every day : school leaders who are making equity a reality - Peterkin, Robert, 1945- (San Francisco, CA : Jossey-Bass, 2011)
'From the prestigious Harvard Urban Superintendents Program, this is a must-have book for new superintendents in large districts, aspiring superintendents, and students of education leadership. It takes readers through the profession of superintendent from entry to exit and includes information on communicating the vision, strategic planning, instructional reform, engaging the community, allocating resources, collaborating with unions and school boards, replicating success, and sustaining improvement. Bolstering each chapter is the Urban Superintendents Program's Leadership Framework, designed to aid administrators and educators in decision making and achieving equity.'--Provided by publisher.
Book is accompanied by one computer optical discs entiltled' Every Child,Every Classroom,Every Day : school leader who are making aquity a reality' bearing the same call number and available at bahagian media.
Includes bibliographical references and index.
System requirements: PC with Microsoft Windows 2003 or later; Mac with Apple OS version 10.1 or later.
Keywords: School superintendents -- United States; School management and organization -- United States; Educational leadership -- United States